Bile salt export pump‐reactive antibodies form a polyclonal, multi‐inhibitory response in antibody‐induced bile salt export pump deficiency. Issue 2 (15th December 2015) - Stindt, Jan; Kluge, Stefanie; Dröge, Carola; Keitel, Verena; Stross, Claudia; Baumann, Ulrich; Brinkert, Florian; Dhawan, Anil; Engelmann, Guido; Ganschow, Rainer; Gerner, Patrick; Grabhorn, Enke; et al.
Abstract : Progressive familial intrahepatic cholestasis type 2 (PFIC‐2) is caused by mutations in ABCB11, encoding the bile salt export pump (BSEP). In 2009, we described a child with PFIC‐2 who developed PFIC‐like symptoms after orthotopic liver transplantation (OLT). BSEP‐reactive antibodies were demonstrated to account for disease recurrence. Here, we characterize the nature of this antibody response in 7 more patients with antibody‐induced BSEP deficiency (AIBD). Gene sequencing and immunostaining of native liver biopsies indicated absent or strongly reduced BSEP expression in all 7 PFIC‐2 patients who suffered from phenotypic disease recurrence post‐OLT. Immunofluorescence, western blotting analysis, and transepithelial transport assays demonstrated immunoglobulin (Ig) G‐class BSEP‐reactive antibodies in these patients. In all cases, the N‐terminal half of BSEP was recognized, with reaction against its first extracellular loop (ECL1) in six sera. In five, antibodies reactive against the C‐terminal half also were found. Only the sera recognizing ECL1 showed inhibition of transepithelial taurocholate transport. In a vesicle‐based functional assay, transport inhibition by anti‐BSEP antibodies binding from the cytosolic side was functionally proven as well. Within 2 hours of perfusion with antibodies purified from 1 patient, rat liver showed canalicular IgG staining that was absent after perfusion with control IgG. Conclusions : PFIC‐2 patients carrying severe BSEP mutations are at risk of developing BSEP antibodies post‐OLT. The antibody response is polyclonal, targeting both extra‐ and intracellular BSEP domains. ECL1, a unique domain of BSEP, likely is a critical target involved in transport inhibition as demonstrated in several patients with AIBD manifest as cholestasis. (Hepatology 2016;63:524–537)